Verbos de movimento e preposições direcionais - Leal, António; Oliveira, Fátima; Silvano, Purificação (Revista da Associação Portuguesa de Linguística, 2017)
The main objective of this paper is to study the semantics of verbs of inherently directed motion (Levin, 1993) ir (‘go’) and vir (‘come’) combined with prepositional phrases with the thematic role of Goal, headed by the prepositions para (‘to) and até (‘to’) in European Portuguese. The data from our news-based-corpus reveals that both prepositions can occur with motion verbs without any apparent restrictions and introduce complements of the verbs ir and vir, although they carry slightly different interpretations: with para, there is a reading that the entity that undergoes movement remains longer in destination than with até. When these prepositions occur within predications that describe non-physical movement, the restrictions increase. The contribution of these prepositions to the determination of the aspectual profile of predications that represent events of movement, namely telicity, poses some theoretical problems, which will also be addressed. This paper puts forward some hypotheses of explanation of the data to be developed in future work.